Evaluating health promotion programs - Valente, Thomas W. (Oxford University Press, 2002)
This is a comprehensive guide to the framework, theories, and techniques used to evaluate health promotion programs. It covers every aspect of the activities involved in conducting an evaluation, including formative, process, and summative research. Particular attention is paid to data collection, management, analysis, and the interpretation of findings.